2020
DOI: 10.1002/ijfe.1854
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Euro through time: Exchange rate dynamics under different regimes

Abstract: In this study, we examine the role of the Euro in currency co‐movements and contagion considering the USD exchange rates of six major currencies (i.e., EUR[DM], JPY, GBP, CHF, AUD, as well as, CAD). We identify five distinct intervals, each one corresponding to a different exchange rate regime or reflecting diverse economic developments. First, we model conditional volatility by introducing a novel DCC‐GARCH‐Copula model (based on GARCH selection criteria). Then, we investigate conditional volatility connected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 113 publications
(119 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, all models allow for different marginal distributions, for example, normal, Student’s t, generalized error distribution (GED), or their skewed versions [ 56 ]. When selecting the most appropriate GARCH specification for each series, we follow an adjusted version of the BIC proposed by Antonakakis et al [ 57 ]: , where L represents the maximum of the likelihood function and k denotes the number of insignificant parameters and the number of significant misspecification tests (including sign bias, the weighted Li-Mak test, the 1% value-at-risk (VaR) test, the 1% conditional VaR test, and the 1% duration based VaR test).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, all models allow for different marginal distributions, for example, normal, Student’s t, generalized error distribution (GED), or their skewed versions [ 56 ]. When selecting the most appropriate GARCH specification for each series, we follow an adjusted version of the BIC proposed by Antonakakis et al [ 57 ]: , where L represents the maximum of the likelihood function and k denotes the number of insignificant parameters and the number of significant misspecification tests (including sign bias, the weighted Li-Mak test, the 1% value-at-risk (VaR) test, the 1% conditional VaR test, and the 1% duration based VaR test).…”
Section: Methodsmentioning
confidence: 99%
“…We departed from the connectedness approach of Diebold and Yilmaz (2014) and performed the relevant analysis in terms of the TVP-VAR model in line with Antonakakis et al (2020), Antonakakis et al (2021), Balcilar et al (2021) Bouri et al (2021), Chatziantoniou and Gabauer (2021). In this context, Gabauer (2021) defines the TVP-VAR model as presented below.…”
Section: Empirical Modelmentioning
confidence: 99%
“…The results further showed that the connectedness between currencies was much stronger, especially in cases of negative and positive shocks. Antonakakis et al (2021), examined the volatility of 6 currencies i.e. Australian dollar (AUD), British pound (GBP), Canadian dollar (CAD), Japanese yen (JPY), Swiss franc (CHF) and Euro (EUR) against the USD.…”
Section: Literature Reviewmentioning
confidence: 99%